PENGARUH MOTIVASI DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA SELAMA PEMBELAJARAN DARING MATA PELAJARAN IPS TERPADU DI SMP NEGERI 23 PEKANBARU - Harliza; Rr. Sri Kartikowati; Hendripides (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article addresses the low learning outcomes in integrated Social Studies (IPS) for eighth-grade students at SMP Negeri 23 Pekanbaru during online learning. The research employed a quantitative descriptive method to examine the effect of learning motivation and learning independence on students’ learning outcomes. The population included all eighth-grade students, with a purposive sample of 78 students from classes VIII B and VIII G. Data analysis was conducted using descriptive statistics, normality, multicollinearity, heteroscedasticity tests, and multiple linear regression via SPSS. The results showed that learning motivation contributed 70.3% to students’ learning outcomes, while learning independence contributed 76.2%. The findings indicate that both learning motivation and learning independence have a positive and significant effect on students’ learning outcomes during online learning, with a combined contribution of 76.2% in integrated IPS subjects.